Views and preferences of patients attending a tertiary hospital in Nigeria on use of saliva for clinical or laboratory tests (2018)
The purpose of this study was to assess the knowledge and views of patients on the use of saliva for clinical or laboratory analysis. This was a cross sectional survey of 189 patients attending one primary and one tertiary oral health facility in Nigeria. Information was obtained from participants using pretested structured questionnaires and SPSS version 23 to analyze the data. Tests of associations between variables were determined using Chi-square and level of significance set at < 5%. One hundred and fifty-two (80.4%) respondents were aware of the use of saliva for clinical or laboratory test. The majority 152 (80.4%) agreed that saliva is easier to collect than other body fluids while 63 (33.3%) preferred to give saliva sample to blood 54 (28.6%) and urine 51 (27%) for clinical or laboratory tests. Only 20 (10.6%) had given saliva for tests before. Ninety-nine (52.4%) indicated strong interest in donating saliva for research while only 4 (2.1%) had given saliva as samples for research work before. Age, educational status and occupational class were significantly associated with awareness of use of saliva as investigative specimen (p < 0.05). This survey revealed that majority of the patients were aware of the use of saliva as well as its advantages over other body fluids for clinical or laboratory tests. Very few indicated previous saliva sampling for clinical and laboratory tests. Thus there is need for development of precise, cheap and accessible saliva tests for patient-centered diagnostic testing and disease monitoring